Effect of continuous positive airway pressure on respiratory drive in patients with obstructive sleep apnea - Radovanovic, Dejan; Rizzi, Maurizio; Airoldi, Andrea; Mantero, Marco; Di Marco, Fabiano; Raccanelli, Rita; Santus, Pierachille (Sleep medicine, 2019)
Patients with obstructive sleep apnea (OSA) have an altered control of breathing during wakefulness. Thus far, whether and how treatment with continuous positive airway pressure (CPAP) may restore these abnormalities has been poorly understood. The aim of this study was to investigate the long-term effects of CPAP on the breathing pattern, ventilatory drive (VDr), and chemoreceptor sensitivity in OSA patients. This was a prospective, observational study, carried out in an academic sleep outpatient clinic. A total of 62 patients with OSA (mean age [SD], 51 [11] years) underwent polysomnography (PSG), breathing pattern assessment, mouth occlusion pressure, ventilatory response to hypoxemia (Ve/SaO2), and hypercapnia (Ve/PETCO2) before and after CPAP titration and during 12-month follow-up. A total of 48 age-matched healthy subjects served as controls. Patients with good (≥6 h/night) and poor (<6 h/night) compliance with CPAP were also compared. At baseline, VDr as well as thoracic and inspiratory impedances were greater in patients with OSA compared with controls and were reduced by CPAP treatment, starting from the night of titration (P < 0.01), especially in patients with good compliance with CPAP. Baseline Ve/SaO2 was higher in OSA patients (P < 0.05) and was progressively normalized during CPAP treatment (P < 0.001). The pathophysiological changes were mainly due to a reduction in tidal volume. The remaining breathing pattern parameters were unaltered by CPAP treatment and were similar between groups. In OSA patients, the mechanics of breathing are inefficient because of an imbalance of the VDr. Regular CPAP treatment improves the efficiency of the respiratory system and normalizes the hypoxemic stimulus. •Obstructive sleep apnea (OSA) patients have increased ventilatory drive compared with healthy subjects.•Increased drive is paralleled by augmented respiratory impedance and hypoxic response.•Regular continuous positive airway pressure (CPAP) use normalizes respiratory impedance and hypoxic ventilatory response.•Monitoring CPAP compliance is essential also in nonobese normocapnic patients.